Bioethics for clinicians: 15. Quality end-of-life care - Singer, P A (1998)
A physician who receives a call from the emergency department to see a patient with heart failure will have a clear framework within which to approach this problem. The thesis of this article is that physicians do not have an analogous conceptual framework for approaching end-of-life care. The authors present and describe a framework for end-of-life care with 3 main elements: control of pain and other symptoms, the use of life-sustaining treatments and support of those who are dying and their families. This 3-part framework can be used by clinicians at the bedside to focus their effort in improving the quality of end-of-life care.